Seuranta YVA- ja ympäristölupamenettelyissä - Mäkelä, Elina (2015)
The aim of environmental monitoring or follow-up is to detect changes in the environment over time and, if needed, to conduct preventive or mitigative actions based on monitoring results to minimize negative environmental effects. In the projects potentially causing significant environmental impacts, follow-up should consist of monitoring program presented in the environmental impact statement (EIS) and of monitoring obligations documented in the environmental permit. In this study, the quality and usability of monitoring programs presented in the EISs of Finnish peat production, crushed stone aggregate and dump projects were investigated. The study was conducted by a three-step content analysis in which the monitoring program presented in the EIS, the monitoring section of the statement on EIS made by an EIA (environmental impact assessment) authority and monitoring obligations written in environmental permits were analyzed. The main research subjects were monitoring parameters and monitoring density presented in EIA monitoring programs and in monitoring obligations of environmental permits. According to the results, monitoring programs were often very general and of poor quality. The majority of monitoring programs were missing monitoring density and parameters. Monitoring obligations in the environmental permits were notably more detailed and numerous compared to the monitoring suggestions of EIS’s monitoring programs. The results of this study show that monitoring programs presented in EISs cannot usually be used in further project planning. To change this, the requirements of the contents of the EIS’s monitoring program should be made clearer either in the Finnish EIA legislation or by writing official EIA or EIS guidelines. Detailed monitoring programs could be used directly as a basis for monitoring obligations or official monitoring programs, and in EIA quality assurance.